The Role Of Organizational Culture In Improving Teacher Performance In Primary Schools - Muzakkir (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to analyze the relationship between organizational culture and teacher performance in elementary schools. This research uses a quantitative descriptive method with a population of all teachers who teach in elementary schools in Lembah Seulawah District totaling 90 teachers spread across 9 schools. The research sample was selected using proportional random sampling. Data was obtained by distributing questionnaires distributed to selected teachers, which contained questions related to organizational culture and teacher performance. Data analysis uses descriptive statistical techniques to describe the characteristics of organizational culture and teacher performance, as well as correlation tests to see the relationship between organizational culture and teacher performance. The results of the Spearman correlation coefficient analysis, found a correlation coefficient value of 0.740, which indicates a strong positive relationship between the two variables. The higher the organizational culture implemented in the school, the better the performance shown by the teacher. Factors in organizational culture, such as shared values, norms, and effective communication, have been shown to have a significant impact on teacher motivation and work quality. With a significance level of 0.000, which is smaller than 0.05, it can be concluded that the relationship between organizational culture and teacher performance is very statistically significant. These findings indicate that organizational culture not only has a positive influence, but is also an important factor in improving teacher performance, which in turn can support improving the quality of teaching and student learning outcomes. Keywords: organizational culture, performance, teachers.